IMPLEMENTASI UNDANG-UNDANG NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT DALAM UPAYA MENGENTASKAN KEMISKINAN (KAJIAN TERHADAP MEKANISME DAN KINERJA LEMBAGA BADAN PENGELOLA ZAKAT DI KOTA SURAKARTA) - Mohammad Adnan; Zeni Lutfiyah; Agus Rianto (Universitas Sebelas Maret, 2014)
The existence of zakat institutions, there are Badan Amil Zakat Nasional (BAZNAS) and Lembaga Amil Zakat (LAZ), is one of the positive response of the government in implementation of zakat management in Indonesia.This research is an empiric research. The location of this research is in BAZNAS Surakarta, Solo Peduli Ummat Foundation and Lazis UNS. This research talks about the mechanism of zakat management in Surakarta starts with collecting until distributing, then about the charitable organizations programs and also about the relation between the organizations performance with the policy of Surakarta City Government in order to reducing poverty.The result of the research and the study show that there are variation and innovation in managing zakat from the zakat institutions in Surakarta start with collecting until distributing. Then the relation between the performance of Surakarta City Government and charitable organizations is very low. It is showed with there is no coordination from both of them that make no synergy of the programs in order to reducing poverty. It is only a few special programs from zakat institutions in order to reducing poverty in Surakarta for example is provision of capital. The use of funds is dominated by charity program or consumptive programs.